PENGEMBANGAN MODUL BERBASIS PEMBELAJARAN SAINTIFIK UNTUK PENINGKATAN KEMAMPUAN MENCIPTA SISWA DALAM PROSES PEMBELAJARAN AKUNTANSI SISWA KELAS XII SMA N I SLOGOHIMO 2014 - Susilo, Agus; Siswandari, Siswandari; Bandi, Bandi (Jurnal Pendidikan Ilmu Sosial, 2016)
Has conducted research on the development of scientific learning-based module to increase the ability to create students in the learning process accounting. Target of trial module is student from XII IPS 1 SMA N 1 Slogohimo in 2014/2015 academic year, while target of modules development is XII IPS 2 (treatment class) and XII IPS Bio (control class) at SMA N 1 Slogohimo in 2014 / 2015 academic year.The test result shows that the instrument is valid to be used for research with excellent value: materials expert 83, 16%, media specialists 84,17% and practitioners 88%. The test results obtained excellent achievement percentage of 85.7%. The results showed that the Economics module in accounting section based on scientific learning approach is effective to improve the ability of creative learners to obtain significant value = 0.007 â‰¤ 0.05 at effectiveness test of the control class and treatment class. Further, the average value of the creating ability in treatment class is 80.45 and control class is 69.17. This value indicates that achievement of the treatment class is higher than the control class